2015
DOI: 10.1186/s12245-015-0074-3
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of indications for neurological consultation in the emergency department

Abstract: BackgroundRecognizing the diverse presentation of neurological conditions that emergency physicians encounter can be challenging, and management of these patients often requires consultation with a neurologist. Accurate diagnosis is critical in neurological emergencies because patient outcomes are often dependent on timely treatment. Our primary objective was to ascertain whether consultant neurologists understood the reason for consultation in the emergency department.MethodsThe authors conducted a prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
7
2
Order By: Relevance
“…The mean LOS in our ED (207 min) was longer than the LOS reported by Linden et al (156 min) but shorter than the LOS reported by Hoyer et al (250 min) and Hansen et al (408 min) [ 1 , 3 , 12 ]. The most frequently observed LOS in our study was 120–240 min (553 patients, 47.9%), and 218 patients (18.9%) stayed in the ED for >360 min.…”
Section: Discussioncontrasting
confidence: 65%
“…The mean LOS in our ED (207 min) was longer than the LOS reported by Linden et al (156 min) but shorter than the LOS reported by Hoyer et al (250 min) and Hansen et al (408 min) [ 1 , 3 , 12 ]. The most frequently observed LOS in our study was 120–240 min (553 patients, 47.9%), and 218 patients (18.9%) stayed in the ED for >360 min.…”
Section: Discussioncontrasting
confidence: 65%
“…Previous studies analyzed neurological examinations in ED focusing on motivations and frequencies of consultation, describing the diagnostic accuracy and the concordance rate between consultants and ED physicians [15][16][17]. Moeller et al 2008 reported that misdiagnosis or diagnostic uncertainly occurred in one-third of all neurological consultations in ED, especially for benign neurological conditions such as migraine.…”
Section: Discussionmentioning
confidence: 99%
“…There are different models for neurologic coverage in EDs such as neurohospitalists or teleneurology and prehospital rescue structures as well as in-hospital resources are quite different from country to country and even hospital to hospital [25]. Thus, each emergency center is forced to align their workup protocol to their current infrastructure and resources at present [10,26,27]. Some of these approaches have a neurological focus [26,28].…”
Section: Discussionmentioning
confidence: 99%